Aquatic biomass (algae) as a future feed stock for bio-refineries: A review on cultivation, processing and products - Bharathiraja, B.; Chakravarthy, M.; Ranjith Kumar, R.; Yogendran, D.; Yuvaraj, D.; Jayamuthunagai, J.; Praveen Kumar, R.; Palani, S. (Renewable & sustainable energy reviews, 2015)
Global outlook of biofuels turns out to be a full-fledged search focusing the viability and sustainability assets. The present day option for immediate and sustainable alternate fuels lies with algal biofuels. Algae are the most sustainable fuel resource in terms of food security and environmental issues. Inefficient and unsustainable biofuel derived from food crops twosome food security issues thus increasing interests towards algal energy. CO2 mitigation, quick biomass accumulation accomplishing simultaneous bioremediation have gathered progressive attention. Cultivation of biomass, harvesting, processing and fuel production by chemical/biochemical reactions are the sequential stages in algal biofuel production. Currently, biofuels produced from algal biomass is not economical since biomass cultivation, processing and separation of fuel products appears costly although certain advancements in culturing techniques have been recently unearthed. Further improvements with the biomass processing strategies may step up the third-generation biofuel concept a profitable one in the near future. This article reviews various cultivation methods, processing techniques and stages in algal biofuel production thereby extensively investigating their potential application in biofuel refineries.